‘The Victim of Death-Rays from Mars’: An Evaluation of ‘gap-filling’ in Tchaikovsky Biographies - Nicholas Ong (Slovo, 2022)
This article assesses the perils of biography through two contentious events in the life of nineteenth-century Russian composer Pyotr Ilyich Tchaikovsky (1840–93). Investigations into the historical often mandate that biographers ‘fill the gap’ in the narratives they are to construct when met with an absence of unequivocal traces, thus rendering the prized truth rather elusive. This has been particularly so for Tchaikovsky whose death – the first of the events studied in this article – has sparked an immediate debate that remains unabated in modern-day music research. The second exploration concerns the sudden cessation of Tchaikovsky’s patron Nadezhda von Meck which had implications for biographers’ narrative rendering of the relationship dynamics between composer and patron. Rather than seeking to establish the ‘truth’, this article concerns itself with the function that the events serve in the overarching narrative presented by the numerous biographers.
Keywords: Music; Tchaikovsky; Biography; Suicide Theory; Musicology; History